THE GEOPOLITICS OF LANGUAGE: HOW LINGUISTIC IDENTITY SHAPES INTERNATIONAL ALLIANCES AND CONFLICTS - Tukhtaeva Zarina (Bright Mind Publishing, 2025)
With an emphasis on how linguistic identity affects international relations, this essay examines the relationship between language and geopolitics. The study shows that language is a potent soft power tool that may influence foreign policy, cultural domination, and national image in addition to being a communication tool. The article illustrates how linguistic strategies impact alliances, conflicts, and global power structures with real-world examples, including China's promotion of Mandarin globally and Russia's use of the Russian language in Eastern Europe.
Keywords: Language geopolitics, linguistic identity, international alliances, soft power.